2020
DOI: 10.1002/suco.202000137
|View full text |Cite
|
Sign up to set email alerts
|

Pushover analysis for flexible and semi‐flexible pile‐supported wharf structures accounting the dynamic magnification factors due to torsional effects

Abstract: This is a pushover analysis for pile‐supported wharves considering the dynamic magnification factors due to torsional effects. The piles seismic design by deterministic approach is shown accounting plastic hinges and P‐delta effects in 2D/3D mathematical modeling. A real structure placed at high seismicity area is considered as case study in order to validate the model and provide reliable technical data. New bound limits of seismic demands associated with damage states and the best soil performance are identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…( 13)). Equation ( 2 non-structural elements (Zacchei et al 2020), whereas ξ d can be estimated more easily since dampers are construct in laboratory, their sizes are small, and the material is homogeneous.…”
Section: Methodsmentioning
confidence: 99%
“…( 13)). Equation ( 2 non-structural elements (Zacchei et al 2020), whereas ξ d can be estimated more easily since dampers are construct in laboratory, their sizes are small, and the material is homogeneous.…”
Section: Methodsmentioning
confidence: 99%
“…The pushover analysis was performed in the 2D FB-FEA, FA-1, and FA-2 models, considering the corrosion effect up to 75 years and constant gravity loads (P = 100 kN). Furthermore, the lateral load (F push ) was applied as a series of displacement-based loads [59] implemented on the top edge of the deck in 1 mm increments until the target displacement was reached. The target displacement was the horizontal displacement of the node at the top of piles A1 and B1 (Figure 9).…”
Section: Pushover Analysismentioning
confidence: 99%
“…This interest exists regarding the seismic hazard for nuclear power plants 16 as well as other constructions of great sizes, for example, dams and bridges. 52 Moreover, many companies work on projects outside Brazil where they must deal with such issues as, for example, the port in Venezuela where the authors of this article have participated to the design as shown in Zacchei et al 36 2 | STRUCTURAL MODEL…”
Section: Motivation Of This Studymentioning
confidence: 99%
“…The structural analysis carried out in this study is elastic, that is, the used static forces are equivalent to the elastic dynamic forces of fixed-base structures. In this sense, for instance, the effects of eccentricities due to lateral torsions that increase the structure response studied in other works 35,36 are not considered.…”
Section: Introduction 1| Backgroundmentioning
confidence: 99%